Implmentasi Pendidikan Karakter Baku (Baik Dan Kuat) Melalui Program SSG (Santri Siap Guna) di Pondok Pesantren Daarut Tauhiid Bandung - ramadansyah, Ramadansyah (UNISBA Press, 2023)
Abstract. Daarut Tauhiid Islamic Boarding School is one of the institutions that handle, especially character building, one of the leading programs in fostering this character is the education and basic training of ready-to-use students in applying BAKU (baik dan kuat) character. This research aims to: 1) know the background of the implementation policy of BAKU (baik dan kuat) character education through the SSG program. 2) BAKU character education for Santri Siap Guna participants. 3) support and inhibite factors for the implementation of BAKU (good and strong) character education through the SSG program. Researcher used descriptive methods to obtain a clear picture of